1996
DOI: 10.1017/s1357729800015101
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factor-1 (IGF-1) and growth hormone-receptor (GHR) mRNA in liver, skeletal muscle and adipose tissue of different breeds of pig

Abstract: The work described was carried out to study the expression of insulin-like growth factor 1 (IGF-1) and growth hormone-receptor (GHR) mRNA in liver, skeletal muscle and adipose tissue from three breeds of pig with varying growth characteristics. The three breeds studied were the Large Wlrite, noted for its lean tissue; the Duroc, characterized by its high intramuscular fat content; and the Meishan X Landrace (0-5 Meishan), noted for its fat, poorly conformed carcass and slower growth rate. The probes used were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It was. also found that major levels of class 2 transcripts (exon 2-containing transcripts) of IGF-I were only present in the liver, a result also found in other whole-animal pig studies looking at differences with age (Brameld et al 1995a) and breed of pig (Brameld et al 1996~). Increased growth rates were accompanied by an increase in the proportion of class 2 IGF-I mRNA in the liver, suggesting a role for class 2 IGF-I in the endocrine growth response.…”
Section: Effects Of Manipulating Energy Availabilitysupporting
confidence: 72%
“…It was. also found that major levels of class 2 transcripts (exon 2-containing transcripts) of IGF-I were only present in the liver, a result also found in other whole-animal pig studies looking at differences with age (Brameld et al 1995a) and breed of pig (Brameld et al 1996~). Increased growth rates were accompanied by an increase in the proportion of class 2 IGF-I mRNA in the liver, suggesting a role for class 2 IGF-I in the endocrine growth response.…”
Section: Effects Of Manipulating Energy Availabilitysupporting
confidence: 72%
“…Even if circulating IGF-I concentrations in gilts were similar between breeds at the end of gestation, the IGF system could still be involved in the different metabolism of the two genotypes. Indeed, even though no differences in liver IGF-I mRNA expression levels were reported at 85 kg BW between breeds, the expression of IGF-I mRNA in muscle and adipose tissue was lower in Meishan than Large White pigs (Brameld et al 1996).…”
Section: Discussionmentioning
confidence: 83%
“…The literature reports no difference in IGF-I concentrations between Meishan (or Meishan crosses) and European breeds at a body weight of 85 kg (Brameld et al 1996), between 10 and 140 d of age (Louveau et al 1991) and at 80 d (Louveau and Bonneau 1996). On the other hand, values were lower in Meishan than LW boars from 20 to 52 wk of age (Weiler et al 1998), and in Meishan than LW pigs at 185 (Louveau and Bonneau 1996;Louveau et al 1991) and 365 d of age (Louveau et al 1991).…”
Section: Discussionmentioning
confidence: 98%
“…However, circulating insulin concentrations have been shown to broadly correlate with circulating IGF-I concentrations (Dawson et al 1998), and thus it is logical to speculate that animals fed dried grass might have had higher plasma IGF-I concentrations. IGF-I production is believed to be associated with the hepatic response to growth hormone, an association modulated by nutritional status (Brameld et al 1996) and insulin (McGuire et al 1995). As IGF-I is believed to mediate the protein anabolic effects of growth hormone (Douglas et al 1991), it is likely that the greater rates of carcass protein gain in animals fed dried grass compared with grass silage were in part mediated by this hormone.…”
Section: Insulinmentioning
confidence: 99%